The Implementation of The Merdeka Curriculum for Englih - Musringatin, Musringatin; Sunggingwati, Dyah; Utami Asih, Yuni (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2025)
The nationwide implementation of Indonesia's Merdeka Curriculum, emphasizing student-centered learning, has limited empirical research that has examined how English teachers navigate the pedagogical transition from traditional teacher-centered approaches in actual classroom contexts. This qualitative case study investigated the implementation experiences of English teachers adopting the Merdeka Curriculum, focusing on their strategies, challenges, and outcomes in transitioning to student-centered teaching approaches. Using purposive sampling, in-depth interviews were conducted with two experienced English teachers at SMP N 9 Loa Kulu, Kutai Kartanegara. Data were analyzed using Miles, Huberman, and Saldana's (2014) interactive model to identify implementation patterns and emerging themes. Findings revealed that both teachers demonstrated a comprehensive understanding of the curriculum's constructivist principles and successfully implemented student-centered strategies through project-based activities, innovative assessment methods, and cultural integration approaches. Teachers effectively fostered 21st-century skills development through collaborative projects and authentic communication practices. However, significant implementation challenges emerged, including assessment transition difficulties, increased material development workload, limited technology resources, and insufficient administrative support. Moreover, despite these obstacles, teachers reported positive learning outcomes, including enhanced student engagement, improved critical thinking, and better collaborative skills. Key recommendations include continuous professional development, improved resource allocation, and stronger institutional support systems. While this small-scale study limits generalizability, it provides valuable insights into the practical realities of curriculum implementation and highlights the critical need for systematic support to achieve the Merdeka Curriculum's transformative educational goals in Indonesian EFL contexts